The influence of external factors on the development of professional burn-out syndrome among nursing personel - Markiewicz, Renata (Current Problems of Psychiatry, 2013)
The article analyses external factors (active burnout) influencing the development of the burnout syndrome in nursing personnel. The factor analysis helped the author to single out those factors which are essential and divide them into six basic groups, i.e. emotional commitment to work, stigmatization of the mentally sick, being overloaded with responsibilities at work, experiencing negative emotions connected with performing duties, exhibiting by nurse eagerness in the workplace, staff appraisal factor. Next, a thorough analysis was made of the correlation between the above factors and some additional ones including: patients aggressive behavior towards nursing personnel, attempted suicides by hospitalized patients and experiencing by nurses pent-up emotions caused by the above-mentioned situations. The purpose of the present paper was to determine the predicative elements of the burnout syndrome in the examined group of nurses. The research was carried out on a group of 60 nurses employed at The Mazovian Specialist Centre in Pruszków, near Warsaw.